Detection of microRNA biomarkers via inhibition of DNA-mediated liposome fusion. Issue 2 (21st November 2018) - Jumeaux, Coline; Kim, Eunjung; Howes, Philip D.; Kim, Hyemin; Chandrawati, Rona; Stevens, Molly M.
Abstract : We report the specific and sensitive detection of microRNA using an inverse DNA-mediated liposome fusion assay. Abstract : We report the specific and sensitive detection of microRNA using an inverse DNA-mediated liposome fusion assay. This assay is homogeneous, and does not require washing, separation, or enzyme-associated amplification steps. By fine-tuning the surface functionalisation of the liposomes, liposome concentration, and assay temperature, we demonstrated a sub-nanomolar limit of detection for the target.